Interference of mouth breathing with orthodontic treatment duration in Angle Class II, Division 1 - Jéssica Antunes RODRIGUES; Bianca Núbia SOUZA-SILVA; Sílvia Elaine Zuim de Moraes BALDRIGHI; Luiz Renato PARANHOS; Carla Patrícia Hernandez Alves Ribeiro CÉSAR
Abstract Introduction Several factors can interfere with orthodontic treatment, and it is important to verify which ones may hinder its success. Objective To compare the duration of orthodontic treatment between nasal and mouth breathers with Angle Class II, Division 1 malocclusion. Material and method This is an analytical observational study which used the records of orthodontic patients cared at a higher education institution in Sao Paulo state, Brazil, between 1999 and 2009. Data from the following variables were analyzed: age, gender, breathing mode (nasal or oral breathing), and treatment duration (beginning and end). Patients were matched for age and treatment used. The ANOVA test was applied to analyze the study data at 5% significance level (p<0.05). Result The study sample consisted of 36 individuals, 16 female (10 nasal breathers and six mouth breathers) and 20 males (eight nasal breathers and 12 mouth breathers), aged nine to 15 years (mean age=13.021). As for orthodontic treatment duration, individuals in the nasal breathing group remained between 27 and 74 months (mean duration=39.61) under treatment, whereas treatment of individuals in the mouth breathing group lasted between 29 and 50 months (mean duration=36.66). No statistically significant differences were observed between the study groups. Conclusions We conclude that the variable altered breathing mode does not interfere with treatment duration.